2016
DOI: 10.1073/pnas.1523968113
|View full text |Cite
|
Sign up to set email alerts
|

B-cell–independent sialylation of IgG

Abstract: IgG carrying terminal α2,6-linked sialic acids added to conserved N-glycans within the Fc domain by the sialyltransferase ST6Gal1 accounts for the anti-inflammatory effects of large-dose i.v. Ig (IVIg) in autoimmunity. Here, B-cell-specific ablation of ST6Gal1 in mice revealed that IgG sialylation can occur in the extracellular environment of the bloodstream independently of the B-cell secretory pathway. We also discovered that secreted ST6Gal1 is produced by cells lining central veins in the liver and that Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 37 publications
12
115
0
Order By: Relevance
“…Recent work has demonstrated that activated platelets release the CMP-Sia that serves as the donor for circulating ST6Gal-I, allowing for the remodeling of the glycans of hematopoietic progenitor cells (Lee et al 2014). Additional in vivo support for the biosynthetic role of circulating ST6Gal-I comes from a recent study showing that ST6Gal-I-deficient B cells express IgGs that are modified with α2,6-sialylated glycans and these are synthesized by circulatory ST6Gal-I released from the liver and CMP-Sia from activated platelets (Jones et al 2016).…”
Section: St6gal-i and St6gal-iimentioning
confidence: 99%
“…Recent work has demonstrated that activated platelets release the CMP-Sia that serves as the donor for circulating ST6Gal-I, allowing for the remodeling of the glycans of hematopoietic progenitor cells (Lee et al 2014). Additional in vivo support for the biosynthetic role of circulating ST6Gal-I comes from a recent study showing that ST6Gal-I-deficient B cells express IgGs that are modified with α2,6-sialylated glycans and these are synthesized by circulatory ST6Gal-I released from the liver and CMP-Sia from activated platelets (Jones et al 2016).…”
Section: St6gal-i and St6gal-iimentioning
confidence: 99%
“…Furthermore, significant shifts in relative levels have been associated with age (all glycosylation features except fucosylation), infection and pregnancy111213141516. The type of glycosylation is dependent on expression levels of glycosyltransferases and glycosidases in the secretion pathway of the antibody-producing plasma B cell17, except for sialylation which is probably also depended on extracellular sialyltransferase expression in the circulation181920. The degree of fucosylation and bisection of IgG is generally very stable, with ~95% serum IgG being fucosylated and ~15% bisected.…”
mentioning
confidence: 99%
“…However, this can only be firmly concluded when general glycosylation patterns of RSV‐specific antibodies made by the infant are known. An alternative explanation for the age‐related changes in glycosylation of RSV‐specific antibodies is extracellular glycan modification of antibodies, but this remains speculative and has thus far only been shown for sialylation . Even for sialylation, most of the incorporated sialic acid is still expected to be assembled in the B cells, as antigen‐specific antibodies formed in certain immune responses can deviate markedly from total IgG …”
Section: Discussionmentioning
confidence: 99%